Significance of chorionicity on long‐term outcome of low birthweight infants of <1500g in twin pregnancies. Issue 8 (6th April 2015) - Kawamura, Hiroshi; Ishii, Keisuke; Yonetani, Naoto; Mabuchi, Aki; Hayashi, Shusaku; Mitsuda, Nobuaki
Abstract Aim The aim of this study was to evaluate the long‐term outcomes of very low birthweight twins by chorionicity and to identify the perinatal predictors for outcomes in the era of laser surgery for twin–twin transfusion syndrome. Material and Methods This was a retrospective single‐center cohort study of twin pregnancy infants <1500 g from 2003 through 2010. During the study period, laser surgery was performed on cases of twin–twin transfusion syndrome. The composite of adverse outcomes at 3 years of age was defined, including death, cerebral palsy, and developmental delay. The association between perinatal factors and adverse outcomes was evaluated by multiple logistic regression analysis. Results A total of 162 infants (79 dichorionic diamniotic twins [DCDA] and 83 monochorionic diamniotic twins [MCDA]) were included in this study. Laser surgery was performed on 11 cases. The rate of adverse outcomes was 13.9% for DCDA and 26.5% for MCDA. The incidence of each outcome for DCDA and MCDA was: cerebral palsy, 1.3% and 4.8%; developmental delay, 8.9% and 9.6%; and death, 3.8% and 14.5%. Gestational age at birth (adjusted odds ratio: 0.69; 95% confidence interval, 0.57–0.84); and anemia at birth (adjusted odds ratio, 10.64; 95% confidence interval, 1.69–66.9) were independent risk factors, whereas chorionicity did not have significance for outcomes. Conclusion The long‐term outcome of very low birthweight MCDA was almost identical to that of DCDA. Gestational age and anemia at birth were independent risk factors for adverse outcomes.